Validation of a landscape‐scale planning tool for cavity‐dependent wildlife. (18th February 2014) - Stojanovic, Dejan; Koch, Amelia J.; Webb, Matthew; Cunningham, Ross; Roshier, David; Heinsohn, Robert
Abstract Tree cavities provide important habitat for wildlife. Effective landscape‐scale management of cavity‐dependent wildlife requires an understanding of where cavities occur, but tree cavities can be cryptic and difficult to survey. We assessed whether a landscape‐scale map of mature forest habitat availability, derived from aerial photographs, reflected the relative availability of mature trees and tree cavities. We assessed cavities for their suitability for use by wildlife, and whether the map reflected the availability of such cavities. There were significant differences between map categories in several characteristics of mature trees that can be used to predict cavity abundance (i.e. tree form and diameter at breast height). There were significant differences between map categories in the number of potential cavity bearing trees and potential cavities per tree. However, the index of cavity abundance based on observations made from the ground provided an overestimate of true cavity availability. By climbing a sample of mature trees we showed that only 5.1% of potential tree cavities detected from the ground were suitable for wildlife, and these were found in only 12.5% of the trees sampled. We conclude that management tools developed from remotely sensed data can be useful to guide decision‐making in the conservation management of tree cavities but stress that the errors inherent in these data limit the scale at which such tools can be applied. The rarity of tree cavities suitable for wildlife in our study highlights the need to conserve the tree cavity resource across the landscape, but also the importance of increasing the accuracy of management tools for decision‐making at different scales. Mapping mature forest habitat availability at the landscape scale is a useful first step in managing habitat for cavity‐dependent wildlife, but the potential for overestimating actual cavity abundance in a particular area highlights the need for complementary on‐ground surveys.